PENERAPAN MODEL PEMBELAJARAN ARTIKULASI UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS MATERI HIDROSFER KELAS VII H SMP NEGERI 3 KARTASURA TAHUN PELAJARAN 2013/2014 - Kurniawati, Septiana Eka (Pendidikan Geografi, 2014)
ABSTRACTSeptiana Eka Kurniawati.THE APPLICATION OF THE MODEL OF ARTICULATION TO IMPROVE THE LEARNING PROCESS AND RESULT IN SOCIAL SCIENCE WITH THE TOPIC OF DISCUSSION OF HYDROSPHERE OF THE STUDENTS IN GRADE VII-H OF STATE JUNIOR SECONDARY SCHOOL 3 OF KARTASURA IN ACADEMIC YEAR 2013/2014. Skripsi: The Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta, July 2014.The objective of this research is to investigate the improvement of learning process and result in Social Science with the topic of discussion of Hydrosphere through the use of the cooperative learning model of the articulation type of the students in Grade VII-H of State Junior Secondary School 3 of Kartasura in Academic Year 2013/2014.This research used the classroom action research. Its subjects were all of the students in Grade VII-H as many as 30. The sources of data of research were the students and their teacher. The data were gathered through in-depth interview, observation, documentation or archives, and test. They were validated by using the method triangulation, and analyzed by using the descriptive comparative technique of analysis. The result of research shows that the application of the cooperative learning model of the articulation type can improve the quality of learning process and result. There is an improvement in both variables from the initial condition prior to the treatment to the final condition following the treatment in Cycle II. The improvement of the learning process from the initial condition to Cycle I has not achieved the performance indicator stipulated, but it is fulfilled in Cycle II. The learning result of the students improves significantly. Prior to the treatment, their average score is 72, and following the treatment it becomes 75 in Cycle I and 78 in Cycle II respectively with the learning completeness of 100%. Thus, the cooperative learning model of the articulation type can improve the quality of learning process and result of the students in Grade VII-H of State Junior Secondary School 3 of Kartasura. Keywords: Articulation Model Learning.